2021
DOI: 10.1111/liv.15100
|View full text |Cite
|
Sign up to set email alerts
|

High serum fibroblast growth factor 21 is associated with inferior hepatocellular carcinoma survival: A prospective cohort study

Abstract: Background & Aims: Epidemiological evidence linking fibroblast growth factor 21 (FGF21) with hepatocellular carcinoma (HCC) prognosis lacked. We aimed to evaluate the associations between serum FGF21 levels and HCC survival in a large prospective cohort.Methods: 825 newly diagnosed, previously untreated HCC patients from the Guangdong Liver Cancer Cohort were enrolled between September 2013 and April 2017. Serum FGF21 levels were measured by ELISA. Liver cancer-specific survival (LCSS) and overall survival (OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This aberrant expression appears to be more favorable for FGF21's binding. Consistently, both liver and serum levels of FGF21 were upregulated in patients with hepatitis, cirrhosis, and liver tumors, and associated with a significantly decreased survival rate in patients with inferior hepatocellular carcinoma 90 . For the carcinogen-induced HCC animal model, increased FGF21 levels were observed in the early and middle stages of tumorigenesis, and also in normal hepatocytes adjacent to the tumor foci, while sharply diminished once cells progressed to malignancy.…”
Section: Fgf21 Is a Promising Biomarker With Pleiotropic Activities I...mentioning
confidence: 67%
“…This aberrant expression appears to be more favorable for FGF21's binding. Consistently, both liver and serum levels of FGF21 were upregulated in patients with hepatitis, cirrhosis, and liver tumors, and associated with a significantly decreased survival rate in patients with inferior hepatocellular carcinoma 90 . For the carcinogen-induced HCC animal model, increased FGF21 levels were observed in the early and middle stages of tumorigenesis, and also in normal hepatocytes adjacent to the tumor foci, while sharply diminished once cells progressed to malignancy.…”
Section: Fgf21 Is a Promising Biomarker With Pleiotropic Activities I...mentioning
confidence: 67%
“…To the best of our knowledge, few studies reported an association between HCC and the expression of FGF21. FGF21 is induced by liver injury and stress and can be a prognostic biomarker to monitor the carcinogenesis of the liver and established as an early diagnostic biomarker for HCC (23)(24)(25). A study reported that higher levels of FGF21 related to worse survival in HCC patients (23).…”
Section: Fgf In Hccmentioning
confidence: 99%
“…FGF21 is induced by liver injury and stress and can be a prognostic biomarker to monitor the carcinogenesis of the liver and established as an early diagnostic biomarker for HCC (23)(24)(25). A study reported that higher levels of FGF21 related to worse survival in HCC patients (23). Finn et al discovered that higher levels of FGF21 associated with shorter overall survival in HCC patients regardless of treatment (97) and they suggested that FGF21 might be an independent prognostic factor for overall survival in HCC (97).…”
Section: Fgf In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its association with obesity and liver injury, the high levels of circulating FGF21 are often linked to different dysfunctional metabolic processes [ 24 ]. About this, higher serum FGF21 levels have been also associated with worse survival in hepatocellular carcinoma (HCC) patients [ 25 ].…”
Section: Introductionmentioning
confidence: 99%